Mental Health Awareness as a Predictor of Academic Performance in Postgraduate Students (International Journal of Scientific Research in Science and Technology, 2025)
Mental health plays a critical role in the academic success of postgraduate students because at this stage they often face with lots of academic pressure, competitive pressures and family expectations. In India, these challenges are heightened by limited mental health resources and cultural stigma. This study explored the relationship between mental health awareness and academic performance among 200 postgraduate students from Rajiv Gandhi University, Arunachal Pradesh. The sample consisted of 100 students from Social Sciences and 100 students from Science & Technology. A Mental Health Awareness Questionnaire (MHAQ) and official Cumulative Grade Point Average (CGPA) scores were used. Results showed a moderate positive correlation between awareness and CGPA (r = .42, p < .001). Students with higher awareness reported better stress management, stronger study habits and greater use of counselling services. The findings suggest that mental health awareness initiatives could help universities improve student well-being and academic outcomes.
Keywords: Mental Health Awareness; Academic Performance; Postgraduate Students; Indian Higher Education; Student Well-Being